Quality Of Work Life and Human Capital Tehadap Kinerja Pegawai Dinas Pendidikan Kabupaten Ogan Komering Ilir - Sukmarini, Sukmarini (Jurnal Ilmu Manajemen, 2011)
The alm of this study is to examine the quality of work life and human capital toward the employee peformance of dinas pendidikan Kabupaten Ogan Komering Ilir simultaneously and partially. The pupulation used in this study  is 37 of dinas pendidikan Kabupaten Ogan Komering Ilir employee. Census is used in this study. Research design is correction. The equation derives from the analysis is Y=3, 142+0, 173X1+0,142X2. Coefficient correlation is 0,814 and R is 0,929. The result reveals that QWL and human capital have significant impac toward employee performance both simultaneously and partially therefore Ho is reject.